The dynamics of religion in public spheres: religious education and religious diversity in Ghana’s public schools - Arthur, Justice Anquandah (Postgraduate Program of State Islamic University (UIN) Salatiga Jl. Lingkar Salatiga Km. 02 Salatiga, Indonesia https://pps.uinsalatiga.ac.id/, 2024)
Ghana's religious diversity and the role of religion in public spheres have given rise to unique approaches in Religious and Moral Education (RME) within public schools. This study investigates how RME is taught and the extent to which it addresses religious diversity, drawing on ethnographic data from eight public schools in Accra. Ethnographic methods, including interviews, observations, and focus groups with teachers and students, are employed to understand the challenges and opportunities in teaching religion in a pluralistic context. Findings reveal an imbalance in the representation of various religions, with dominant faiths often overshadowing minority beliefs, particularly Indigenous Religions. Teachers' religious affiliations sometimes influence classroom discourse, leading to an inaccurate portrayal of